Psychiatric symptoms and leptin in obese patients who were bariatric surgery candidates - Changchien, Te-Chang (Neuropsychiatr Dis Treat, 2015)
OBJECTIVE: There is a significant relationship between obesity and common mental symptoms (depression and anxiety symptoms). But the association between depression (or anxiety symptoms) and serum leptin is still unclear and controversial, despite the growing body of evidence supporting the existence of “leptin resistance” in obese persons. So we investigated whether common mental symptoms, obesity, and the interactive effect of these two factors have a relationship with leptin in obese patients who were candidates for bariatric surgery. METHODS: In all, 139 participants (mean age: 31.4 years, standard deviation: 9.3 years, 73.4% female) were enrolled at an obesity treatment center in southern Taiwan. Serum leptin levels and body mass index (BMI) were measured. The Chinese Health Questionnaire and Taiwanese Depression Questionnaire were administered. RESULTS: The mean BMI of our participants was 39.4 kg/m(2) (±6.8), and the mean leptin level was 24.5 ng/mL (±9.4). In the multivariate regression models, Chinese Health Questionnaire-by-BMI and Taiwanese Depression Questionnaire-by-BMI interaction terms remained significant predictors of leptin level (β=0.16, P<0.0001; β=0.04, P<0.0001, respectively), after adjustment for age, sex, and history of hypertension, diabetes, and hyperlipidemia, despite the inverse correlation between Chinese Health Questionnaire (or Taiwanese Depression Questionnaire) and leptin. In addition, female patients had significantly higher leptin levels than male patients. CONCLUSION: The present findings confirmed that the relationship between common mental symptoms and leptin is modulated by obesity in severely obese patients. Future studies should focus on further measures of leptin receptors or signaling on the basis of these interactive effects in psychiatry.